Taxane diterpenes .3. Formation of the eight-membered B-ring by semi-pinacol rearrangement - Magnus, P; Diorazio, L; Donohoe, T; Giles, M; Pye, P; Tarrant, J; Thom, S (1996)
The substituted furan carboxaldehyde 15 was converted into enone 20 via a stereoselective intramolecular pyrylium ylide-alkene cyclization. Subsequent elaboration of 20 into the triflate 23, followed by solvolysis in acidic trifluoroethanol resulted in quantitative rearrangement to the taxane B/C core 24. At a higher oxidation level 27 was ring expanded to give 28. The ring expanson strategy could also be initiated by β-elimination of the 3α,10α-oxido bridge. Treatment of 50 with MeOH at reflux gave 52. Similar transformations in the 7-oxy series resulted in ring B expansion of 67 to give 68, and 75 to give 76.